"Plunging into the Mire of Corruption and Pleasure": Niq Mhlongo's Way Back Home. Issue 2 (3rd July 2019) - Kenqu, A Yolisa
Abstract : This article presents a close reading of Niq Mhlongo's Way Back Home, particularly its representation of the post-apartheid nation-state as a place of excess or, indeed, what James Ogude might call a "a site of eating". To begin, I locate Mhlongo's oeuvre within the long and rich tradition of black-centred artistic expression that is preoccupied with black masculinities and the politics/performance of 'hustling'. Turning to Way Back Home specifically, I argue that the novel functions as a critique of the excesses, including the kleptocracy, of the ruling elite. I show that the novel ultimately reveals the underside of South Africa's euphoric discourse of the 'Rainbow Nation'. I wish to evoke not only his novel's interrogation of the notions of home, belonging, desire and the unheimlich in post-apartheid South Africa, but also the sense in which failure is always already a certainty in postcolonial states which adopt and function within structures that were never designed for African progress.